STUDENTS’ PERCEPTIONS OF THE USE THE SHADOWING TECHNIQUE AT MTS NEGERI 1 BITUNG - Rumpa, Inayah Salsabilla; Rombepajung, Paula; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to determine the perceptions of students about the use of the Shadowing technique, especially in the aspect of speaking at MTs Negeri 1 Bitung. Thirty students from MTs Negeri 1 Bitung’s class 9F contributed data to the study. The questionnaire that served as the data collecting method for this study comprised three indications of the use of shadowing techniques: student attitudes, frequency of utilizing the shadowing technique, and the advantages or benefits of using the shadowing approach. The following are the outcomes of a study done on students’ perceptions of the shadowing technique: The majority of students gave a positive response of 70% to the first indicator about student attitudes toward the use of the Shadowing Technique, followed by a positive response of 63% to the second indicator about the frequency of use of the Shadowing Technique, and a positive response of 68% to the last indicator. Of the three data are in the vulnerable 61% - 80%. It is possible to conclude that students’ perceptions of the use of shadowing techniques, particularly in speaking aspect, are Good.